Influence of pH on antimicrobial activity of organic acids against rabbit enteropathogenic strain of Escherichia coli - Skrivanová, E; Marounek, M (Folia microbiologica, 2007)
Susceptibility of the rabbit enteropathogenic strain Escherichia coli C6 (O128 serogroup) to C6-C14 fatty acids, oleic, citric, lactic and fumaric acid at 5 mg/mL was determined by the plating technique in the near-neutral pH region (pH approximately 6.5), and in a weakly acid and acid environment (pH 5.4 +/- 0.1 and 2.2-2.5, respectively). In the near-neutral pH region caproic and caprylic acid reduced the concentration of viable cells by 3 and 6 orders, respectively. At lower pH the bactericidal effect of caproic acid remained similar, but caprylic acid decreased the concentration of viable cells to < 100/mL. The bactericidal activity of capric acid was low at pH 6.5 but increased at pH 5.3. High environmental acidity was intrinsically bactericidal and at very low pH the effects of fatty acids were thus less pronounced. Citric acid reduced the counts of viable cells to 1/10. Antimicrobial activity of other acids examined was marginal or absent. Medium-chain fatty acids, caprylic and, to a lesser extent, also caproic and capric acid were better antimicrobials than other organic acids examined; the antimicrobial activity of fatty acids toward the C6 strain was pH-dependent. Beneficial effects of citric, lactic and fumaric acid reported by animal nutritionists are thus probably related to factors other than their direct antimicrobial action.
Keywords: Caprylates; kyselina citronová; Colony Count, Microbial; infekce vyvolané Escherichia coli; kapryláty; Organic Chemicals; mastné kyseliny; antibakteriální látky; Microbial Sensitivity Tests; kyseliny karboxylové; počet mikrobiálních kolonií; Escherichia coli Infections; Hydrogen-Ion Concentration; Citric Acid; organické látky; Escherichia coli; Fatty Acids; králíci; koncentrace vodíkových iontů; Animals; Anti-Bacterial Agents; zvířata; mikrobiální testy citlivosti; Rabbits; Carboxylic Acids